Married CEOs and Stock Price Crash Risk - Jeong-Bon Kim; Shushu Liao; Yangke Liu (Queen's University Belfast, Queen's Management School, 2021)
This study examines whether marriage, as a social construct and cultural norm, can affect firm-level stock price crash risk. We find that firms managed by married CEOs are associated with lower future stock price crash risk, after controlling for a set of firm characteristics and CEO traits. We document that CEO marriage reduces crash risk by curbing bad news hoarding and formation activities. Moreover, the attenuating impact of CEO marriage on crash risk is more pronounced among firms with weaker corporate governance and those run by less prominent, higher-delta, and lower paid CEOs.
Keywords: G12; G30; M52; M12; 330; Marriage; CEO; crash risk; bad news hoarding; corporate governance; compensation